The Contribution of Islamic Economics to the Equal Distribution of National Income in Padangsidimpuan - Ahmad Toib Daulay; Winda Sari Siregar; Jamudi Jamudi; Abd Halim Dalimunthe; Uswatun Hasanah (International Journal of Community Service Implementation, 2026)
Inequality in income distribution remains a structural problem in national economic development, including in mid-level urban areas such as Padangsidimpuan City. Islamic economics exists not only as a normative economic system but also as a practical approach that emphasizes distributive justice, social solidarity, and support for vulnerable groups. This study aims to analyze the contribution of Islamic economics in promoting equitable distribution of national income at the local level through a case study in Padangsidimpuan City. The research method used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation studies of Islamic economic institutions such as BAZNAS, private zakat institutions, sharia cooperatives, and sharia-based micro, small, and medium enterprises (MSMEs). The results show that Islamic economic instruments, particularly zakat, infaq, sadaqah, and sharia financing, contribute significantly to increasing the income of the poor, expanding access to business capital, and reducing economic inequality. However, this contribution remains partial due to institutional limitations, low sharia economic literacy, and weak integration with regional development policies. This study recommends strengthening synergies between local governments and Islamic economic institutions as a sustainable strategy for income equality.